Comparison of the muscle fascicle length between resistance-trained and untrained individuals: cross-sectional observation - Fukutani, A.; Kurihara, T. (SpringerPlus, 2015)
Background: Muscle plasticity is an important topic in the fields of sport science and physical therapy. The purpose of this study was to examine whether muscle fascicle length increases with resistance training through a comparison between resistance-trained and untrained individuals. If a hypothesis that fascicle length increases by resistance training is true, fascicle length should be longer in the resistance-trained individuals than in the untrained individuals.